Efficacy of a Hospital Discharge Transition Plan in the care competence of patients with chronic conditions and their family caregivers: a clinical trial - Yuliana Valentina Rincón-Estrada; Astrid Nathalia Páez-Esteban; Maria Stella Campos de Aldana; Erika Yurley Durán-Niño; Juan Sebastian Rincón-Contreras; Maria del Pilar Castillo-Galvis; Valeria Arias Pinzón; Sergio Andrés García Arenas (Universidade de São Paulo, 2024)
Objective: to assess the efficacy of a Hospital Discharge Transition Plan in the care competence and in adherence to the therapy of dyads comprised by patients with non-communicable chronic diseases and their caregivers. Method: a controlled and randomized clinical trial; the sample was comprised by 80 dyads of patients with chronic conditions and their caregivers, randomly allocated as follows: 40 to the control group and another 40 to the intervention group. The instruments to characterize the patient-caregiver dyad, the patients' and caregivers' care competence and the patients' adherence to the treatment scale were applied. The " CUIDEMOS educational intervention" was applied to the intervention group; in turn, the control group was provided usual care with the aid of a booklet, with phone follow-up via at month 1. Results: 52.5% of the patients and 81.3% of the caregivers were women. The patients' and caregivers' mean ages were 69.5±12.6 and 47.5±13.1 years old, respectively. The Hospital Discharge Transition Plan increased the scores in the "knowledge", "uniqueness", "instrumental", "enjoying", "anticipation" and "social relations" dimensions, as well as the global care competence of the patients and family caregivers; in addition to the following factors: medications, diet, stimulants control, weight control, stress management, and global adherence to the therapy by the patient. There were no statistically significant differences between the control and intervention groups. Conclusion: the Hospital Discharge Transition Plan increased the patients' and family caregivers' care competence after the intervention, as well as the patients' adherence to the treatment. However, there were no differences between the control and intervention groups, possibly due to the similarity of the activities.